An experimental investigation on light-weight concrete blocks using vermiculite. (2020) - Naveen Kumar, K.; Vijayan, D.S.; Divahar, R.; Abirami, R.; Nivetha, C.
Abstract: Lightweight concrete block finds a wide range of application within the construction industry. Concrete block having a dry density of approximately 300 kg/m 3 to a most of 2000 kg/m 3 are deliberate to be light-weight concrete. By using the lightweight concrete can reduce the self-weight of the structure. Thereby it reduces the price of construction. During this study No fine concrete is employed it's a combination of cement, water, and coarse aggregate with fines (sand) omitted. The concrete mix has cement, coarse aggregate and vermiculite. Fine aggregate is completely neglected. Three trail mix is followed as 1:1:2, 1:1.5:1.5 and 1:2:1. The cubes are casted and tested within the compression testing machine. The take a look at results are compared with IS 2185-1 (2005) observe whether those concrete blocks will be utilized in the construction method.